The effect of Green Product, Green Perceived Value, and Environment Knowledge on Green Purchase Intention on Cleo Eco Green bottled water in Islamic Economic Perspective - Kirana, Sari; Zuliansyah, A.; Devi, Yulistia (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to determine the effect of green product, green perceived value, and environment knowledge on green purchase intention in Cleo Eco Green bottled water products in the perspective of Islamic economics. The method used is a quantitative approach with data collection through questionnaires involving 100 respondents in the city of Bandar Lampung. The results of the analysis showed that Green products have no significant effect on Green Purchase Intention, with a p-value of 0.600. The Green Perceived Value also had no significant effect, with a p-value of 0.070. However, Environment Knowledge was shown to have a positive and significant effect on Green Purchase Intention, with a p-value of 0.033. These findings indicate that although consumer awareness of green products is still low, good environmental knowledge can increase the purchase intention of green products. In the perspective of Islamic economics, these three variables are interconnected and can increase consumer awareness to consider the social and environmental impact of their choices.